Advances in liquid crystals : selected, peer reviewed papers from the 2009 International Symposium on Liquid Crystal Science and Technology, August 2-5, Kunming, China, ISLCST2009 - International Symposium on Liquid Crystal Science and Technology (2009 : Kunming, China); Huang, Yuanming (Stafa-Zurich, Switzerland ; United Kingdom ; Enfield, NH : Trans Tech)
Includes bibliographical references and index.